Assessment of attitudes and goals regarding cosmetic procedures among individuals aged 18 to 28 - Kadir Küçük; Selda Pelin Kartal (Turkderm Turkish Archives of Dermatology and Venereology)
Background and Design: The number of cosmetic procedures is increasing, and currently, young people are undergoing more procedures. Personal and social factors underlie this, and social media has been added. This study evaluates the judgements of young individuals between 18 and 28 years old about their faces and cosmetic procedures from a dermatological aspect. Materials and Methods: Individuals aged 18 to 28 who visited our clinic were included. The data collected using the prepared questionnaire were analyzed using SPSS 25.0. The statistically significant p value is below 0.05. Results: Individuals who desire facial changes report higher levels of dissatisfaction. Women are more likely to express dissatisfaction and desire cosmetic procedures. Childhood teasing is associated with a greater desire to undergo surgery. Personal opinions and social influences play a significant role in decision-making. Income, education, and family factors may influence perceptions of cosmetic procedures. Dissatisfaction with appearance is associated with cosmetic procedures. Conclusion: Cosmetic procedures are positively received in the 18-28 age group. Personal opinion is the most critical factor in decisionmaking, but social circles and the internet are also influential. The scores were similar in terms of necessary, luxury, and unnecessary. Individual expectations are at the forefront rather than social media and the internet's influence. Healthcare institutions are the primary source for consultation and treatment, but the internet is the second most common source of information.